Performance of innovation platforms in crop-livestock agro-ecosystems of the Volta basin in Burkina Faso - Ayantunde, Augustine A.; Swaans, Cornelis P.M.; Some, Hubert W.; Pali, Pamela N.; Douxchamps, Sabine; Ouattara, K. (CGIAR Challenge Program on Water and Food, 2013)
Linear approach to research has had limited success in sub-Saharan Africa and there is need for participatory approach. The CPWF Volta Basin Development Challenge project on integrated management of rainwater in crop-livestock systems (V2) took an overarching innovation platform approach that supports learning and exchange for action research and for scaling up and out of promising best fit rainwater management strategies. Innovation platforms (IP) comprising of multi- stakeholders were established by the project in the project sites in Burkina Faso and Ghana in mid-2011; regular quarterly meetings were organized to identify and prioritize constraints and opportunities to rainwater management in crop-livestock systems and the implementation of strategies to address them. To ensure adequate documentation of IP processes and activities, and for evaluation of the performance of the IPs, monitoring and evaluation tools were developed comprising of register of actors, IP meeting and activity report, and members’ assessment of the IP. The data collected during the IP meetings in the project sites in Ghana was of relatively low quality. Hence, the results reported in this paper were from data collected from IP meetings in Burkina Faso. This paper focused on the assessment of the IP functioning in terms of consistency of participation across meetings and stakeholder groups, relevance/interest of IP issues, participation in decision making, information exchange, facilitation and perceived benefits of IP activities. Results from the assessment of the IPs showed that attendance at the meetings ranged from 24 to 42 participants, of which at least 60% were men. In terms of the groups of the participants, the producers accounted for between 30 and 65% of the total participants at the IP meetings in both locations. Other actors in the IPs included trader, processor, credit agency, technical services, researcher and development agency. All the key stakeholders were consistent in participation at the IP meetings except for credit agency in Koubri. Major activities carried out by the IP in Koubri and Ouahigouya as reported by the members included training, soil and water conservation initiatives, linkage to financial and technical services, supply of agricultural inputs, group marketing particularly of onion, animal management and post-harvest management. From the members’ assessment of IP 1 activities, processes and outputs, gender only had significant effect in the score for participation in decision making where women gave lower score than men. For all the indicators for the IP meetings, the lowest score (2.53±0.16; score was from 1 (lowest) to 5 (highest)) was observed for the quality of facilitation in Ouahigouya for the meeting of March 2012 while the highest score (4.90±0.06) was for conflict resolution in the IP in Ouahigouya for the meeting in June 2013. Also, for all the indicators the mean scores tended to increase with the lifespan of the IP, that is the longer the lifespan the higher the scores given by the members for its performance. These results suggest that IP approach is not a ”quick- win” approach. This raises the challenge of maintaining the interest and participation of relevant actors.